Effect of computer‐aided colonoscopy on adenoma miss rates and polyp detection: A systematic review and meta‐analysis. Issue 2 (11th December 2022) - Shah, Sagar; Park, Nathan; Chehade, Nabil El Hage; Chahine, Anastasia; Monachese, Marc; Tiritilli, Amelie; Moosvi, Zain; Ortizo, Ronald; Samarasena, Jason
Abstract: Background and Aim: Multiple computer‐aided techniques utilizing artificial intelligence (AI) have been created to improve the detection of polyps during colonoscopy and thereby reduce the incidence of colorectal cancer. While adenoma detection rates (ADR) and polyp detection rates (PDR) are important colonoscopy quality indicators, adenoma miss rates (AMR) may better quantify missed lesions, which can ultimately lead to interval colorectal cancer. The purpose of this systematic review and meta‐analysis was to determine the efficacy of computer‐aided colonoscopy (CAC) with respect to AMR, ADR, and PDR in randomized controlled trials. Methods: A comprehensive, systematic literature search was performed across multiple databases in September of 2022 to identify randomized, controlled trials that compared CAC with traditional colonoscopy. Primary outcomes were AMR, ADR, and PDR. Results: Fourteen studies totaling 10 928 patients were included in the final analysis. There was a 65% reduction in the adenoma miss rate with CAC (OR, 0.35; 95% CI, 0.25–0.49, P < 0.001, I 2 = 50%). There was a 78% reduction in the sessile serrated lesion miss rate with CAC (OR, 0.22; 95% CI, 0.08–0.65, P < 0.01, I 2 = 0%). There was a 52% increase in ADR in the CAC group compared with the control group (OR, 1.52; 95% CI, 1.39–1.67, P = 0.04, I 2 = 47%). There was 93% increase in the number of adenomas > 10 mm detected per colonoscopy with CAC (OR 1.93; 95% CI, 1.18–3.16, P < 0.01, I 2 = 0%). Conclusions: The results of the present study demonstrate the promise of CAC in improving AMR, ADR, PDR across a spectrum of size and morphological lesion characteristics.